A Bifunctional Highly Efficient FeNx/C Electrocatalyst. Issue 8 (11th January 2018) - Li, Erling; Yang, Fa; Wu, Zhemin; Wang, Yong; Ruan, Mingbo; Song, Ping; Xing, Wei; Xu, Weilin
Abstract: Herein, a type of Fe, N‐codoped carbon electrocatalyst (FeN x /C, Fe‐N‐BCNT#BP) containing bamboo carbon nanotubes and displaying bifunctional high catalytic efficiency for both oxygen reduction reaction (ORR) and carbon dioxide reduction reaction (CO2RR) is reported. It shows high electrocatalytic activity and stability for both the ORR process with onset potential of 1.03 VRHE in alkaline and the CO2RR to CO with high faradic efficiency up to 90% and selectivity of about 100% at low overpotential of 0.49 V. For CO2RR to CO, it is revealed that Fe3 C is active but the activity of FeN x centers is lower than that of C–N‐based centers, contrary with that observed for ORR. Due to its low cost and high electrocatalytic performance for these two reduction reactions, the obtained catalyst is very promising for extensive application in future. The revealed huge activity difference of the same types of active sites for different reactions can efficiently guide the synthesis of advanced materials with multifunction. Abstract : A type of cost‐effective Fe, N‐codoped carbon electrocatalyst is reported displaying bifunctional high catalytic efficiency for both oxygen reduction reaction and carbon dioxide reduction reaction. It is further revealed that the main electrocatalytic active sites for these two different reduction reactions are different in structure.